Pengaruh Inovasi dan Kualitas Pelayanan Terhadap Kepuasan Masyarakat Pengguna Layanan Samsat Drive Thru: Indonesia - Timbul Dompak; Sahat Sianturi; Naufal Alfian Supratama (Prodi Ilmu Administrasi Negara, 2018)
This study aims to determine the effect of Innovation (X1) and Service Quality (X2) to Satisfaction of Service Users of Samsat Drive Thru (Y). This study uses a quantitative approach by distributing questionnaires to people who are paying vehicle taxes using Samsat Drive Thru service. This research uses 100 accidental sampling technique. The data analysis used is multiple linear regression. The discussion of this research will be obtained from the data processing result from the questionnaire processed with SPSS Version 21. From the results of the data conducted shows the value of coefficient of determination (R2) of 0.617 which means the variable of Innovation and Service Quality able to explain 61.7% variable Satisfaction Users Samsat Drive Service Thru and the rest 38.3% are influenced by other variables not examined in this study. The conclusions from the results of this study indicate that: (1). Partially that Innovation Affects User Satisfaction (t count = 2.396> t table = 1.984); (2). Partially that Service Quality Affects User Satisfaction (t count = 6.352> t table = 1.984); (3). Simultaneously Innovation and Service Quality have a significant effect on User Satisfaction (Fcount = 78,148> Ftabel = 3.09)